Teaching English Language through Literature - Marasini, Nabin Chandra (NUTA Journal, 2019)
This paper seeks to examine the importance of literature in the English language classroom and looks at the effect of its use. Examples given will be mainly from personal experience gained from teaching Nepalese students. It is necessary to understand the importance of teaching English Language through literature in order to make language learning an enriching experience for students. The growing trend of learning English in Nepal has increased its significance as well. The uses of literature in the classroom explore the interesting uses of words, phrases and sounds in contexts. It, then, without human intervention increase students’ awareness of literary language and help them understand language better.